A case report of Villar's nodule in a woman without surgical history. (2018) - Ouédraogo, Nabonswindé Lamoussa Marie; Ilboudo, Safy; Ouattara, Abdoul Karim; Ouedraogo, Aimé Sosthène; Zida, Maurice; Zongo, Nayi; Obiri-Yeboah, Dorcas; Ouangre, Edgard; Simpore, Jacques; Traore, Si Simon
Highlights: We report a case of umbilical endometriosis with unusual clinical expression in woman with no know history of endometrios. There was a gradual transformation of the umbilicus originally normal appearance into several small nodules. The patient underwent mini-omphactomy with uneveventful postoperative course. Abstract: Introduction: Villar's nodule is an umbilical endometriosis without anterior or ongoing pelvic endometriosis. The primitive location of this nodule at the umbilical level is rare. Its etiopathogenesis remains unclear. Presentation of case: We report a case of umbilical endometriosis with unusual clinical expression in a woman in the reproductive years with no surgical history and no known history of endometriosis. Endometriosis manifested as progressive transformation of the normal umbilicus into several small nodules, with bleeding coinciding with the menstrual cycle. The diagnosis was confirmed by histology and surgical treatment consisted of omphalectomy. Discussion: Umbilical endometriosis is a rare disease that occurs naturally in patients with pelvic endometriosis. Etiopathogenesis of the disease is still unclear. In our patient, the appearance of the nodule was impressively, by a gradual transformation of the normal aspect of the umbilicus, into several small, slightly pigmented, firm, painful and concomitantly bleeding nodules during periods of menstruation. In the literature, this multinodular or budding form would be of exceptional observation. Conclusion: The characteristics of the umbilical tumor, associated with the cyclical nature of tumor bleeding in a patient without previous history of endometriosis, strongly suggest the diagnosis of Villar's nodule, but the confirmation is still histological. The treatment is always surgical and recurrence is very rare.